The Impact of Digitalization on Productivity and Economic Performance in the Industrial Sector - Ridwan Ridwan; Hapzi Ali (Greenation Publisher, 2024)
Digitalization has become an important part of the global economic transformation, impacting various fields, including the manufacturing sector. The focus of this research is how digitalization impacts economic performance and productivity in the industrial sector in Indonesia. It has been shown that productivity, operational efficiency, and financial performance improve by using secondary data obtained from websites and online papers that utilize digital technology in their operations. There is evidence that technologies such as automation, the Internet of Things (IoT), big data, and artificial intelligence (AI) can help businesses become more efficient and competitive. This result shows that digitalization is a key factor in facing competition in Industry 4.0.